The Analysis of English Textbooks for Senior High School towards The Characteristics of Microlearning - Ariyanti, Sartika Dwi; Seli, Fenny Yutika (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The COVID-19 pandemic has fundamentally changed the face of English language teaching, creating both obstacles and opportunities for students and teachers. Since textbooks play an important role in providing organized and complete learning materials, this study aims to examine the requirements of English textbooks for twelfth-grade high schools that use microlearning features. The goal is to investigate the feasibility of using microlearning as an effective strategy for textbook use in English language teaching for twelfth-grade students in Indonesia. This study is an analytical study that focuses on several aspects of textbooks. The alignment with the curriculum, the relevancy of material, the appropriateness of teaching techniques, and the fit for the requirements and characteristics of twelfth-grade high school students are all key topics of inquiry. Furthermore, the study investigates the extent to which these textbooks meet local cultural norms and expectations, ensuring that Indonesian English learners have a meaningful learning experience. The outcomes of this study shed light on the strengths and shortcomings of the selected textbooks, offering useful insights into their effectiveness in supporting English language acquisition. Moreover, the report makes pertinent recommendations for prospective enhancements and future research paths